EVALUASI PELAKSANAAN REMEDIAL MATA PELAJARAN EKONOMI PADA SISWA KELAS XI SMA NEGERI 2 PONTIANAK - Nevirianti, Nevirianti; Achmadi, Achmadi; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractTitle of this thesis is "Evaluation of the Implementation of Remedial Learning in Economic Subjects in Class XI Students of IIS SMA 2 Pontianak". A common problem in this thesis is "Evaluation of the implementation of remedial learning for economic subjects in class XI IIS". Sub problems are what are the steps in implementing remedial learning and how are student learning outcomes after the implementation of economic subjects remedial learning in class XI IIS of SMA Negeri 2 Pontianak. The data collection tool used in this paper is an observation and interview guide. The analysis in this thesis was presented in a qualitative descriptive manner by using informants from economic subject teachers and IIS XI graders in Pontianak 2 Public High School. The results of this study indicated that the implementation of remedial learning is not effective enough because the teacher does not pay attention to the steps of remedial learning according to existing procedures, especially in the plan of remedial activities and the results of student scores on economic subjects after following remedial activities progress, this showed that activities Remedial has helped students who have difficulty in understanding learning materials and achieving completeness in learning outcomes. Keywords: Economic subjects, Evaluation, implementation of remedial learning